Shear-reducing Insoles to Prevent Foot Ulceration in High-risk Diabetic Patients - Constantinides, Georgios; Lavery, Lawrence A.; LaFontaine, Javier (My University, 2012)
OBJECTIVE: The objective of this study was to evaluate the effectiveness of a shear-reducing insole compared with a standard insole design to prevent foot ulceration in high-risk patients with diabetes. RESEARCH DESIGN AND METHODS: A total of 299 patients with diabetic neuropathy and loss of protective sensation, foot deformity, or history of foot ulceration were randomized into a standard therapy group (n = 150) or a shear-reducing insole group (n = 149). Patients were evaluated for 18 months. Standard therapy group consisted of therapeutic footwear, diabetic foot education, and regular foot evaluation by a podiatrist. The shear-reducing insole group included a novel insole designed to reduce both pressure and shear on the sole of the foot. Insoles were replaced every 4 months in both groups. The primary clinical outcome was foot ulceration. The authors used Cox proportional hazards regression to evaluate time to ulceration. RESULTS: There were 2 significant factors from the Cox regression model: insole treatment and history of a foot complication. The standard therapy group was about 3.5 times more likely to develop an ulcer compared with shear-reducing insole group (hazard ratio, 3.47; 95% confidence interval, 0.96-12.67). CONCLUSIONS: These results suggest that a shear-reducing insole is more effective than traditional insoles to prevent foot ulcers in high-risk persons with diabetes.
Keywords: Diabetic neuropathies; Foot--Ulcers; Patients